Effective Laboratory Management: Efforts to Improve Science Education Management in Islamic Boarding Schools - Anugriaty Indah Asmarany; Djunaedi; Abdul Azizul Hakim; Arif Saefudin; Loso Judijanto (Jurnal Penelitian Pendidikan IPA, 2024)
Effective laboratory management can be applied as an effort to improve science education management in secondary schools. This study aims to explore effective laboratory management as an effort to improve science education management at MA Citra Cendekia South Jakarta. The research method used was a descriptive qualitative method with a case study approach. Data were collected through direct observation, in-depth interviews with teachers and laboratory staff, and analysis of related documents. The results showed that effective laboratory management involves several important aspects, namely careful planning, procurement and maintenance of adequate laboratory equipment, and competency development of teachers and laboratory technicians. In addition, collaboration between science teachers and laboratory staff in designing and conducting experiments also contributes significantly to improving the quality of science learning. The implementation of good laboratory management at MA Citra Cendekia South Jakarta is proven to be able to increase student learning motivation, improve understanding of science concepts, and produce more interactive and contextualised learning. This study concludes that effective laboratory management is one of the key factors in improving the quality of science education in Islamic educational institutions.